Distance Entrepreneurship Education as an Essential Strategy to Empower Indonesian Migrant Workers - Tanan, Antonius (Jurnal Entrepreneur dan Entrepreneurship, 2012)
The purpose of the entrepreneurship training is to empower learners to be entrepreneurs and when this learning process is delivered by online learning it will create much more flexibility. The training can be delivered from the home country where there is no language barrier, it is cheaper than traditional face-to-face training, it can be accessed at any time, and the content is a homeland context. This study aims to explain the training process by distance learning which is administered by Ciputra University Entrepreneurship Centre at Hongkong. The training is then strengthened by ICT infrastructure, communication strategy and comprehensive learning strategy. The result shows that there is a significant change on the entrepreneurship skills of Indonesian workers, therefore the role of government is needed to to support this significant result (the involvement, government policies, campaign of distance learning, and the comprehensive making of user friendly hardware and software).